Development aid and disease discourse on display: the mutating techniques of neoliberalism. Issue 1 (1st January 2017) - Kwitonda, Jean Claude
ABSTRACT: The objective of this essay is to explore the ascendency of discourse in the practice of international development and communication. Two cross-currents in the contemporary discourse of international development, namely development aid and the notoriously variegated concept of neoliberalism, have coalesced in a discourse crisis. This is due largely to competing understandings of neoliberalism – as either a hegemonic project, policy and program, a state form, or governmentality. I will argue that the complexity of development aid and the process of social change in general cannot be reduced to a single understanding of neoliberalism. However, considering neoliberalism as discourse provides a more encompassing framework. This frame has considerable advantages for understanding processes of social change and development aid. The paper will also show that the framework is attuned to the mutating techniques of neoliberalism and discuss the potential of this framework for guiding participation in international development.